To stop the progress of antimicrobial resistance today means to give a chance of mankind surviving tomorrow - Kozlov R.S.; Golub A.V. (Клиническая микробиология и антимикробная химиотерапия, 2019)
Antimicrobial resistance is a global challenge for human society. Scientists around the world are trying not to return to the time when antimicrobials were not yet discovered, and millions of people were dying from infections. This article describes the current state of the antimicrobial resistance problem in Russia as well as the ways to solve it.